1965
DOI: 10.1021/j100885a020
|View full text |Cite
|
Sign up to set email alerts
|

The Kinetics of Ion Association in Manganese Sulfate Solutions. I. Results in Water, Dioxane-Water Mixtures, and Methanol-Water Mixtures at 25°

Abstract: Ultrasonic absorption has been measured in water, dioxane-water, and methanol-water solutions of MnS04 at 25°. The three-peak relaxation spectrum is interpreted by the three-step association between Mn+2(aq) and SOv-2(aq) proposed by Eigen. All six rate constants for the three-step process are calculated by a straightforward method.Step I is diffusion controlled with a forward rate constant of 4.2 X 10 ~1 sec.-1 in water while the step III forward rate (4.g X 107 sec.-1) seems controlled by the rate of exchang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

1967
1967
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(20 citation statements)
references
References 2 publications
1
19
0
Order By: Relevance
“…2 The calculations use a computer program (Cohen and Colman, 1972) with values of 57.6 and 1150 M-1 for the association constants of manganous ion with dibasic and tribasic isocitrate (Grzybowski et al, 1970). Corrections were made for the association of manganous ions with chloride (Aa = 3.7 M-1) (Grzybowski et al, 1970), with acetate ions (Aa = 15.8 M_1) (Vallee and Wacker, 1970), with sulfate ions (A"a = 139 M-1) (Atkinson and Kor, 1965), and with Mes (Aa = 5 M_l) (Good et al, 1966). FIGURE 3: Lineweaver-Burk plots of the variation of the velocity of oxalosuccinate decarboxylation with manganous ion concentration in the presence and absence of coenzymes.…”
Section: Resultsmentioning
confidence: 99%
“…2 The calculations use a computer program (Cohen and Colman, 1972) with values of 57.6 and 1150 M-1 for the association constants of manganous ion with dibasic and tribasic isocitrate (Grzybowski et al, 1970). Corrections were made for the association of manganous ions with chloride (Aa = 3.7 M-1) (Grzybowski et al, 1970), with acetate ions (Aa = 15.8 M_1) (Vallee and Wacker, 1970), with sulfate ions (A"a = 139 M-1) (Atkinson and Kor, 1965), and with Mes (Aa = 5 M_l) (Good et al, 1966). FIGURE 3: Lineweaver-Burk plots of the variation of the velocity of oxalosuccinate decarboxylation with manganous ion concentration in the presence and absence of coenzymes.…”
Section: Resultsmentioning
confidence: 99%
“…[25] This has significant implications since it was then possible to determine the kinetics and the corresponding energies for the ion pairing process. [26][27][28] Since ILs and organic electrolytes tend to exhibit a markedly more diverse interaction landscape than the non-specific electrostatic interactions found in e. g. simple metal halide electrolytes, Hunt et al categorized interactions in ILs as Hbonds of three types. [29] The neutral H-bond X•••Y, the ionic Hbond [X] + ,À •••Y between an ion and a neutral molecule and the double ionic H-bond [X] + •••[Y] À between two ions.…”
Section: Introductionmentioning
confidence: 99%
“…Bjerrum further considered that ion pairs and free ions in solution will be in thermodynamic equilibrium and hence the law of mass action and an equilibrium association constant could be defined [25] . This has significant implications since it was then possible to determine the kinetics and the corresponding energies for the ion pairing process [26–28] …”
Section: Introductionmentioning
confidence: 99%
“…Detailed studies (2)(3)(4)(5)(6) have since shown that the stepwise ion association in aqueous solutions of 2-2 electrolytes could account for the absorption in excess of that expected from viscous losses. The assignment of mechanism was aided by a study of mixed solvent solutions of these salts (7) ; there are, however, still some discrepancies in both the data and its interpretation (4)(5)(6). The low concentration of ion pairs in aqueous solutions of 1-1 electrolytes excludes their showing an excess absorption except at salt concentrations much higher than that found in sea water (8).…”
Section: Introductionmentioning
confidence: 99%